HUBUNGAN ANTARA KEMAMPUAN LITERASI DENGAN KOMPETENSI INTI PENGETAHUAN BAHASA INDONESIA SISWA KELAS V SD GUGUS LETKOL WISNU DENPASAR UTARA TAHUN PELAJARAN 2017/2018 - Ni Ayu Made Yulina Sari (Indonesian Journal Of Educational Research and Review, 2018)
This study aimed to determine the significant relationship between the literacy skills with the core competency of knowledge of Indonesian language students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018. This research is ex post facto research with correlation type. The population of this study is a class V student residing in SD Gugus Letkol Wisnu, North Denpasar Lesson Year 2017/2018 which has a population of 340 people. Determination of the sample used proportional random sampling technique with significant level 5% and obtained the number of samples from the population is 172 people. The data were obtained through the multiple-choice objective test of the literacy skills and the document recording of the core competency of knowledge of Indonesian language student. As the test is a normality test data distribution. After all prerequisite tests are met, the statistical analysis used in this next study is hypothesis test using product moment correlation analysis. Based on result of analysis then  = 0,227. At the significant level of 5% with n = 172, then obtained  = 0.148. Because  >  =  0.227 >  0.148 it can be interpreted that H₀ which reads there is not significant relationship between literacy skills with the core competency of knowledge of  Indonesian language students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018 is rejected and  accepted. So it can be concluded that there is a significant relationship between literacy skills with the core competency of knowledge of Indonesian language students of grade V SD Gugus Letkol Wisnu, North Denpasar, in the Lesson Year 2017/2018, with a positive correlation direction, meaning the higher literacy skills then the higher the core competency of knowledge of Indonesian language students. Keywords : Literacy skills, the core competency of knowledge, Indonesian